2019
DOI: 10.1186/s13068-019-1548-y
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the carbohydrate-binding module on the activity of a fungal AA9 lytic polysaccharide monooxygenase on cellulosic substrates

Abstract: Background: Cellulose-active lytic polysaccharide monooxygenases (LPMOs) secreted by filamentous fungi play a key role in the degradation of recalcitrant lignocellulosic biomass. They can occur as multidomain proteins fused to a carbohydrate-binding module (CBM). From a biotech perspective, LPMOs are promising innovative tools for producing nanocelluloses and biofuels, but their direct action on cellulosic substrates is not fully understood. Results:In this study, we probed the role of the CBM from family 1 (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
56
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(68 citation statements)
references
References 50 publications
(62 reference statements)
7
56
0
3
Order By: Relevance
“…The obtained K M -and k cat -values of NcLPMO9C and the variant LPMOs were similar to previously published values [36]. In contrast to the recently published work by Chalak and coworkers [32], we were able to successfully produce an active LPMO variant with a truncated linker and CBM1 right after the catalytic domain. However, this modification resulted in a partial reduction of the thermostability.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…The obtained K M -and k cat -values of NcLPMO9C and the variant LPMOs were similar to previously published values [36]. In contrast to the recently published work by Chalak and coworkers [32], we were able to successfully produce an active LPMO variant with a truncated linker and CBM1 right after the catalytic domain. However, this modification resulted in a partial reduction of the thermostability.…”
Section: Discussionsupporting
confidence: 88%
“…When looking at the regioselectivity on cellulosic substrates, NcLPMOs 9F, 9C and 9M share the same product pattern as previously published [19]. In contrast to Chalak and coworkers [32] no change in the regioselectivity of the enzyme was observed when removing the CBM1. However, recent efforts to elucidate the role of a family 2 CBM linked to LPMO10C from Streptomyces coelicolor revealed no change in regioselectivity upon truncation of the CBM2 from the enzyme [26].…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Domain similarity network analysis has shown the correlation between the additional domains and the substrate specificity of the full enzymes (Book et al 2014;Zhou et al 2019b). CBM truncation studies have been reported for both LPMO9s and LPMO10s (Chalak et al 2019;Courtade et al 2018;Crouch et al 2016;Forsberg et al 2016;Laurent et al 2019). Comparison of the performance of LPMOs with and without CBMs have shown that, deletion of CBMs reduced LPMO's binding capacity to crystalline substrates, especially at low substrate concentrations.…”
Section: The Appended Modulesmentioning
confidence: 97%